Failure analysis of laser cladded AISI 4340 remanufactured steel - Khalid Aljahsyi Mahmood (2014)
The sustainability benefits that remanufacturing concept brings about has called upon the need to further develop a sound understanding behind this technology. In this presented study, the primary focus is to investigate the detrimental effects of the clad layer on the fatigue performance of the laser cladded AISI 4340 remanufactured steel with AISI 4340 steel powder. The experimental fatigue testing carried out on the above material exhibited lower fatigue performance as compared to its substrate thus microstructural studies and fracture analysis were conducted. 4 single and 1 multiple clad specimens were tested for its microhardness. Results showed a declining trend in the clad hardness across the clad layer of the multiple clad specimen. The first clad bead recorded hardness value similar to single-clad specimens but reduces, gradually, with every consecutive adjacent clad beads. The inconsistent microhardness distribution could result in an uneven stress distribution during loading process, and hence lowers fatigue performance. Subsequently, 5 such specimens were subjected to different cyclic loading conditions and placed under scanning electron microscopy (SEM). Observation on the fractured surfaces indicated that the fatigue process was initiated from the clad layer with origins lying mainly within the surface proximity of the clad. It also revealed imperfections to the cladding process such as inclusions which increases stress concentration factor thus influencing the type of crack propagation within the specimen. Further observations along the clad-substrate interface revealed a decent bonding between the clad and substrate but with microcracks, voids and microvoid coalescence existing along the interface. It is therefore concluded that the clad layer acts a source of fatigue initiation which lowers the fatigue performance of the laser cladded AISI 4340 remanufactured steel with AISI 4340 steel powder.